Modelling of rammed earth under shear loading - Silva, Rui André Martins (2014)
The intensive use of earth as a building material since ancient times resulted in an important and significant earthen built heritage currently existing worldwide spread. The rammed earth technique has a significant presence in this heritage, where it served to build from simple dwell-ings to fortresses. However, the high vulnerability of rammed earth constructions to decay agents and to seismic events puts in risk their further existence and the lives of millions of peo-ple. With respect to the seismic behaviour of rammed earth walls, the understanding and mod-elling of their shear behaviour are topics underdeveloped in the bibliography. Nevertheless, these topics are of extreme importance in the preservation and strengthening of rammed earth constructions. Therefore, this paper presents a numerical work aiming at modelling the non-linear behaviour of unstabilised rammed earth under shear loading, resorting to the finite ele-ments method (FEM). The models were used to simulate the behaviour of a set of rammed earth wallets tested under diagonal compression. Both macro- and micro-modelling approach-es were considered, where the objective of this last approach was to evaluate the influence of apparent weakness of the interfaces between layers on the shear behaviour. The total strain ro-tating crack model (TSCRM) was used to simulate the behaviour of the rammed earth material, while the Mohr-Coulomb failure criterion was used to simulate the behaviour of interfaces be-tween layers. Furthermore, uncertainties related to the definition of the input parameters re-quired performing a sensitivity analysis. The numerical models achieved good agreement with the experimental results and the compressive strength, the Poisson’s ratio, the tensile strength and the tensile fracture energy revealed to be the most important parameters in the analyses.